Pengaruh Asimetri Informasi, Ukuran Perusahaan dan Corporate Governance terhadap Manajemen Laba pada Sektor Konsumsi (BEI) Tahun 2019-2022 - Isnawati, Maulida; Ulupui, I Gusti Ketut Agung; Mardi; Murdayanti, Yunika (Jurnal Akuntansi, Perpajakan dan Auditing, 2023)
The purpose of this study is to examine whether Information Asymmetry, Company Size and Corporate Governance have an influence on Earning Management. The population which is used as the object of this study are companies from the non-cyclicals consumer sector that are listed on the Indonesia Stock Exchange (IDX) in 2019 - 2022. Out of a total of 98 population, there are 65 companies that meet the criteria to be used as sample in this study. The results of this study indicate that: (1) Information Asymmetry has a significant positive effect on Earning Management, (2) Company Size has no significant effect on Earning Management, (3) Corporate Governance has a significant negative effect on Earning Management.